Germinative response of redroot pigweed (Amaranthus retroflexus L.) to environmental conditions: Is there a seasonal pattern?. (3rd May 2016) - Cristaudo, A.; Gresta, F.; Restuccia, A.; Catara, S.; Onofri, A.
Abstract : Experiments on redroot pigweed ( Amaranthus retroflexus L.) were conducted to investigate whether the germinative response to environmental conditions is affected by the time of seed set. Seeds were collected in the same field (Sicily, Southern Italy) in May, July and October; each lot was dry-stored from 15 to 400 days after harvest (DAH) and submitted to germination assays from 15 to 40°C, both in continuous darkness (D) and in alternate light/darkness regime (L/D). For the three lots, over 15 DAH, the response to temperature and light regime was strongly affected by harvesting time. Seeds set in May, negatively affected by L/D, showed a high germination capability (>80%) at 95 DAH from 25 to 40°C. Seeds set in July were favoured by L/D and required at least 170 DAH to reach 80% germination capability. Seeds set in October were also favoured by L/D and gave a good germination capability only at 300 and 400 DAH. These results prove that seed germination behaviour in redroot pigweed is not independent of the time of the year in which seeds are produced and is due to both the environmental conditions experienced by the mother plant during seed maturation and those experienced by seeds after seed set.